Climate changes: effects of secondary salinisation in freshwater organisms - Leitão, João Luís Vieira (2013)
As global climate patterns change, so will freshwater availability. Specially, salinisation of freshwater costal ecosystem is a major point of concern; either by surface flooding or by groundwater intrusions of seawater. This may be potentiated by the decrease of freshwater availability provoked by longer drought periods, evaporation, and increased freshwater extraction (for example for agriculture and other human uses). According, the present work aimed at evaluating how freshwater organisms responded to an increase in salinity. To achieve this main objective two specific goals were delineated: (i) to compare the toxicity of seawater with a surrogate (NaCl), commonly used in laboratory toxicity assays, to two standard freshwater species, and (ii) to assess if an association exist between resistance to chemical contamination and to increased salinity; since many populations, predicted to experience future increased salinity, are presently exposed to chemical contamination. To accomplish the first objective the sensitivity of the green algae Pseudokirchneriella subcapitata (Korshikov) F. Hindák and of the cladoceran Daphnia magna Straus to NaCl and to natural seawater was evaluated. Growth rate for P. subcapitata, and mortality, time to release the first brood, body size, total reproduction, and intrinsic rate of natural increase for D. magna, were monitored after exposing these species to two series of solutions with an increasing gradient of salinity. One series of solutions was established with a natural seawater sample and the other with NaCl dissolved artificial media. To address the second objective, four cloned lineages of Daphnia longispina O.F. Müller, exhibiting different sensitivities to lethal levels of copper, were exposed to a gradient of lethal and sublethal levels of salinity, established with the salt NaCl. The same endpoins described for D. magna were also monitored for D. longispina. The obtained results showed that NaCl exerted a higher toxicity to P. subcapitata (LOEC of 5.9mS/cm and 9.6mS/cm, respectively for NaCl and seawater) and to D. magna (LC50,48h of 9.88mS/cm and 11.32mS/cm; and EC50 for total reproduction of 8.9mS/cm and 10.4mS/cm, respectively for NaCl and seawater) than the natural seawater. These data suggest that the use of NaCl as a surrogate for seawater to predict, in laboratory, the effects of seawater intrusion in freshwater is a protective approach as it simulates a “Worst Case Scenario” of exposure. An association between resistance to copper and to NaCl was not observed for the tested cloned lineages of D. longispina (r < 0.92 and p > 0.08), though the two clonal lineages most resistant to copper also exhibited the highest sensitivity to sublethal levels of NaCl (determined as the EC20 for total reproduction). Finally, obtained data demonstrated that D. longispina was more sensitive to increased salinity (LC50,48h of 2.85g/L to 2.48g/L or, conductivity values of LC50,48h of 5.50mS/cm to LC50,48h= 4.57mS/cm which correspond respectively to the highest and lowest recorded values in these assays) than the standard species (D. magna), highlighting the importance of using autochthonous species for the ecological risk assessment of secondary salinisation.